Efficacy and safety of cemiplimab in cutaneous squamous cell carcinoma on chronic wounds: A French retrospective study - M. Antoszczak; E. Maubec; A.-B. Duval-Modeste; A. Jannic; C. Jacobzone-Leveque; R. Lesbazeilles; F. Skowron; D. Solub; J. Ancel; L. Mortier; M. Viguier (EJC Skin Cancer)
Background: Chronic wounds increase the risk of the development of cutaneous squamous cell carcinoma (SCC), often resulting in poor prognosis in part because of delayed diagnosis. Cemiplimab, an anti-PD-1 agent, is recommended as first-line treatment for metastatic or locally advanced SCC not eligible for curative surgery, chemotherapy or radiation. However, its efficacy in SCC originating from chronic wounds remains uncertain. Objective: This retrospective study assessed the efficacy and safety of cemiplimab in patients with SCC originating from chronic wounds. Methods: We included patients receiving cemiplimab for SCC on chronic wounds between August 2018 and January 2021. The primary endpoint was progression-free survival (PFS) determined by Kaplan-Meier analysis. Secondary endpoints included response rate and safety. Results: We included 17 patients, predominantly female (59 %), with median age 58 years (interquartile range 49–77). SCC typically originated from leg ulcers (47 %) and presented at locally advanced (41 %) or metastatic stage (41 %). With cemiplimab, often received as third-line therapy (41 %), the median PFS was 6.1 months (95 % confidence interval [CI], 2.97–7.70), with the best response rate 47 % and complete response rate 12 %. We found immune-related adverse events in 24 % of cases. Short PFS was associated with distant metastasis at treatment initiation. Conclusion: Despite response rates comparable to other SCC types, median PFS was low with cemiplimab treatment for SCC originating from chronic wounds, likely due to the aggressive nature and/or high frequency of altered performance status. Anti-PD-1 therapy remains a primary treatment option for inoperable cases. Further prospective studies are warranted to confirm these findings and optimize treatment strategies.